1982
DOI: 10.1002/hep.1840020609
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Igm Antibodies to Hepatitis B Core Antigen in Hepatitis B Carriers and Hepatitis B–Associated Chronic Liver Disease

Abstract: IgM antibody to hepatitis B core antigen (IgM anti‐HBc) was determined in 60 patients whose serum was positive for hepatitis B surface antigen (HBsAg) and 18 patients whose serum was negative for HBsAg, but positive for antibody to hepatitis B core antigen (anti‐HBc). Two radioimmunoassays were done utilizing either anti‐u antibody to capture IgM or Staphylococcus A protein to separate IgG and IgM. Both methods failed to detect IgM anti‐HBc in 30 healthy carriers, 5 HBsAg‐positive cirrhotics, 2 patients with H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

1983
1983
1994
1994

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 16 publications
2
10
0
Order By: Relevance
“…Very few similar cases have been reported up to now [Kryger et al, 19811, although the potential clinical value of the anti-HBc IgM assay in differentiating acute hepatitis B patients from HBsAg carriers. who develop acute hepatitis caused by different agents, has been implied by several investigators [Feinman et al, 1982;Gitnick, 1983;Shimizu et al, 19831. Such false positive diagnoses of acute type B hepatitis may have exaggerated the risk of an adult becoming an HBsAg carrier following primary acute HBV infection IDcinhardt and Gust, 19821.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Very few similar cases have been reported up to now [Kryger et al, 19811, although the potential clinical value of the anti-HBc IgM assay in differentiating acute hepatitis B patients from HBsAg carriers. who develop acute hepatitis caused by different agents, has been implied by several investigators [Feinman et al, 1982;Gitnick, 1983;Shimizu et al, 19831. Such false positive diagnoses of acute type B hepatitis may have exaggerated the risk of an adult becoming an HBsAg carrier following primary acute HBV infection IDcinhardt and Gust, 19821.…”
Section: Discussionmentioning
confidence: 96%
“…Contrasting results have been reported regarding the diagnostic value of various anti-HBc IgM assays used to differentiate acute from chronic HBV infection. Thus the estimated prevalence of anti-HBc IgM in asymptomatic HBsAg carriers has ranged from 34.9 to 100% in some studies [Gerlich et al, 1980: Hawkes et al, 1980Schalm et al, 1980;Kryger et al, 1981;Lemon et al, 1981;Roggendorf at al, 19811, while other investigators have found no anti-HBc IgM activity [Cohen, 1978;Tedder and Wilson-Croome 1980;Feinman et al, 1982;Shimizu et al, 19831. Discrepancies have also been reported in the ability of assays to distinguish between recent and past HBV infection in HBsAg-negative patients [Cohen, 1978;Gerlich et al, 1980;Hawkes et al, 1980;Tedder and Wilson-Croome, 1980;Kryger et al, 1981;Lemon et 1981; Roggendorf et al, 1981;Feinman et al, 1982;Shimizu et al, 19831.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Others found no detectable IgM anti-HBc in such patients [Feinman et al, 1982;Shimizu et al, 1983;Papavangelou et al, 19841.…”
Section: Introductionmentioning
confidence: 97%